The dynamic relationship between exchange rate, interest rate and stock market; comparison between ASEAN5 and ASEAN5+3 - Mahmoud Moustafa Radi, Shaimaa (2018)
The global market has been witnessing great volatility which gave importance to estimating the linkage among economic and financial variables and their response to shocks, making it a major concern for both policymakers and investors. Among these markets; the ASEAN5, along with their major trading partners, Plus Three (China, Japan and Korea) are gaining attention in trade, domestic and foreign investment, creating a need to understand how major variables are interrelated in this market. Therefore this study examines the joint dynamic relationship between exchange rate (against USD), interest rate and stock market, investigating the effect of innovation on the linkage comparing between ASEAN5 and ASEAN5+3 from 2007:9 to 2017:3. For this purpose causality, VAR, VECM, Impulse response and Variance decomposition were employed. The results showed there is long run relation between the variables in ASEAN5 based on VECM, a result not confirmed in ASEAN5+3, although there is cointegration. A negative relation exists between exchange and interest, while the direction was not confirmed with stock. The lag values of exchange rate do not have predictive power over stocks in ASEAN5+3. In the short run convergence to and divergence from equilibrium was found in ASEAN5+3 and ASEAN5 respectively. Innovation to stock negatively affects exchange rate and interest rate in both markets. Changes in stock do not immediately affect exchange rate in ASEAN5, whereas in ASEAN5+3 was stock own innovations accounted for most of the variation. Therefore, policymakers need to reduce intervention but also be in control when needed and investors are advised to diversify to reduce risks.